MEMOAR RASA TAKUT DALAM DIRI SEBAGAI SUMBER PENCIPTAAN SENI GRAFIS - Dimas Bayu Setiawan; Theresia Agustina Sitompul (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
Departing from the author's empirical experience about the memoir of fear in oneself and experiencing scary and sad events, the writer wants to know himself more deeply. the creation of a work of graphic art this final project is to create a work of graphic art that takes the inspiration of fear, which indirectly also explains the concept of its creation, as well as the visual aesthetics of the work of graphic art, with the aim of creating the work of graphic art itself. The creation of the work refers to three stages, namely finding the initial idea, developing, perfecting and strengthening the initial idea. The result obtained from the creation of this work is self-therapy using high print art media.